THE READABILITY OF ENGLISH TEXTBOOK FOR THE TENTH GRADE STUDENTS OF SMK NEGERI I BINJAI - Floridawaty Siregar; Anni Holila Pulungan; Sortha Silitonga (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
This research was aimed to find out whether the English reading texts are appropriate or not in terms of the readability level for the tenth grade students of SMK Negeri 1 Binjai. This study focuses on the readability level of English reading texts for grade X students of SMK Negeri 1 Binjai majoring in Banking class in the academic year 2015/2016. This study is categorized as descriptive quantitative research. The data of the study was seven reading texts from an English textbook entitled Bahasa Inggris published by Kementerian Pendidikan dan Kebudayaan in 2014 with various length and genres as the source of data tested to 30 students as the research sample. The instruments of the research were Flesch-Kincaid Grade level and Cloze Procedure Test. For the Flesch-Kincaid Grade Level Formula, the researcher counts the words, syllables, sentences, the average number of words per sentence and the average number of syllables per words of the reading text to determine the level of readability of the English texts in students’ textbook. The cloze test was used to assess the difficulty in terms of a reader’s understanding and response to the structure of the language of a text. The results of the study show that based on the cloze test result, the researcher gets the average score of 7 reading texts is 57.39% and based on the Flesch-Kincaid Grade Level Formula the average score is 6 so it can be concluded that reading texts of Bahasa Inggris published by Kementerian Pendidikan dan Kebudayaan in 2014 are in the Independent level because the reading texts are readable and understandable to the tenth grade students of SMK Negeri 1 Binjai, and the texts are predicted to be quite easy. Therefore, the researcher takes a conclusion that this textbook is not appropriate to be used by the students at the tenth grade students of SMK Negeri 1 Binjai because they can read them by their own. Keywords : Readability, English Textbook, Students of SMK Negeri 1 Binjai.